2012
DOI: 10.1007/s00586-012-2533-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior correction of thoracic adolescent idiopathic scoliosis with pedicle screw instrumentation: results of 48 patients with minimal 10-year follow-up

Abstract: Purpose Since early 1990s pedicle screws in thoracic spine have been used in posterior correction of adolescent idiopathic scoliosis (AIS). Long-term results are scarce. We report clinical, radiological and pulmonary function results of 48 consecutive patients with 10-year minimal follow-up. Methods Forty-eight consecutive patients (42 females, 6 males) with 41 Lenke 1 (lumbar modifier A = 19, B = 8, C = 14), 7 Lenke 2 (lumbar modifier A = 2, B = 4, C = 1) were operated for AIS from posterior with pedicle scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 21 publications
3
23
0
2
Order By: Relevance
“…A recent prospective cohort study with 10-year follow-up conducted by Min et al [44] has shown good correction with a pedicle screw implant density of 50 %. High implant density has not shown improvement in patient reported outcomes [38][39][40][41][42][43][44] or cosmesis [39], and has contributed to less thoracic kyphosis [38,40,41], and high costs [42,45]. In contrast to what might be expected, it was shown through a finite element analysis and computational study that high implant density does not improve the distribution of forces and correction [46,47].…”
Section: Supporting Empirical Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…A recent prospective cohort study with 10-year follow-up conducted by Min et al [44] has shown good correction with a pedicle screw implant density of 50 %. High implant density has not shown improvement in patient reported outcomes [38][39][40][41][42][43][44] or cosmesis [39], and has contributed to less thoracic kyphosis [38,40,41], and high costs [42,45]. In contrast to what might be expected, it was shown through a finite element analysis and computational study that high implant density does not improve the distribution of forces and correction [46,47].…”
Section: Supporting Empirical Evidencementioning
confidence: 98%
“…Some studies have shown slightly larger radiographic correction with high implant density [38][39][40], while others have shown no correlation between implant density and curve correction [41][42][43]. A recent prospective cohort study with 10-year follow-up conducted by Min et al [44] has shown good correction with a pedicle screw implant density of 50 %. High implant density has not shown improvement in patient reported outcomes [38][39][40][41][42][43][44] or cosmesis [39], and has contributed to less thoracic kyphosis [38,40,41], and high costs [42,45].…”
Section: Supporting Empirical Evidencementioning
confidence: 99%
“…The use of pedicle screws at all vertebral levels led to the reassessment of the role of posterior-only arthrodesis as treatment for severe scoliosis [16,17]. Recent studies [18] have shown a correction rate in severe scoliosis treated by all-screw posterior instrumentation to be around 50 %, which is similar to the correction rate obtained by combined approach surgery. Di Silvestre et al [19] compared two similar series of patients with severe thoracic idiopathic scoliosis (main curve over 80°Cobb), the first treated by posterior hybrid instrumentation fusion and the second by posterior all-screw instrumentation fusion, with a mean follow-up of 6.7 years.…”
Section: Introductionmentioning
confidence: 95%
“…To compare the preoperative stiffness of the curves, the flexibility % was calculated, with no difference in the groups (p > 0.05). The mean postoperative thoracic Cobb curve angle was 15.81º (±5.28), 21.63º (±6.89), and 27.55º (±8.25), respectively. The mean correction of the thoracic curve was 68.87% in the screw group, 58.76% in the hybrid and 50.27% in the hook group.…”
Section: Resultsmentioning
confidence: 99%